Analysis of Administrative Staff Workload in Public Service Institutions that Support Public Education - Yopie Purwa Nugraha; Slamet Suwanto (Civiliza Publishing, Indonesia., 2025)
Public services at the sub-district level require proportional employee workload management for effective organizational performance. However, in Regolwetan Sub-district, South Sumedang District, an imbalance in workload among employees is still found, impacting service quality. This study aims to analyze employee workload, identify inhibiting factors, and determine solutions for improvement. The research method used was qualitative with a descriptive approach through in-depth interviews, observation, and documentation. The results indicate that the workload is not evenly distributed, especially among public service employees with high work volumes. The main obstacles include limited human resources, suboptimal delegation of authority, inadequate work facilities, and additional tasks beyond job functions. This study concludes that workload analysis in Regolwetan Sub-district is not optimal and requires a reorganization of task distribution to improve employee performance and the quality of public services.